GTPase-Dependent Mechanointegration of Shear-Mediated Cell Contractility Through Dynamic Binding of FLNa and FilGAP - Bergeron-Sandoval, L. P.; Cai, Alex; Clouvel, Anna; Hitti, Cynthia; Ehrlicher, Allen (Frontiers in Physics, 2022)
Cellular mechanotransduction is a common mechanism by which cells convert mechanical cues (or stimuli) from their environment into biochemical and cellular responses. In the case of shearing forces, such as when individual cells encounter interstitial shear stress and blood shear stress, mechanotransduction is proposed to begin through mechanical stretching and spatial reconfiguration of Filamin A (FLNa) binding sites and subsequent release of FilGAP molecules normally bound to FLNa. However, the connection and importance of downstream molecular effectors and cellular metrics involved in response to shear stress are not understood. Here we reveal mechano-sensitive GTPase-mediated changes in cell contractility. By varying expression of FilGAP, and expression of FLNa, we show that microfluidic shear stress results in cell contractile changes only when FilGAP and FLNa dynamically bind and dissociate. By using FRET sensors that quantify the Rho or Rac charge state, we demonstrate that only cells with dynamic FLNa and FilGAP convert shear stress into GTPase activity, and the resulting downstream contractile changes. Finally, we show that manipulation of Rho and Rac through pharmacological means rescues the -contractile activity, in the absence of intact FLNa-FilGAP mechanosensing. This research clarifies a precise mechanomolecular pathway used for cellular force sensing and may play critical roles in human health challenges from cancer metastasis to cardiovascular disease.